Eastern African breeding research partners - and ultimately farmers - benefit from breeding research improvements that reduce cost and improve performance - CGIAR Research Program on Maize (2021)
Molecular technologies provide the ability to predict and select families and individuals prior to field testing, increasing genetic gain per unit cost of investment. Forward breeding and genomic selection are now routinely applied in maize breeding pipelines in eastern Africa. The cost savings of molecular tools enabled the CGIAR and national breeding programs to evaluate a larger number of new maize lines, improving the odds of delivering higher performing hybrids in the future.